MICRONUTRIENT STATUS (VITAMINS A AND D) AND ITS EFFECT ON THE SEVERITY OF THE COURSE OF COVID-19 IN CHILDREN - Г. Павлишин; О. Лабівка; К. Козак (Bukovynian State Medical University, 2024)
A strong immune response is important during recovery from COVID-19, and its status is infl uenced by several micronutrients. Vitamin D is important in regulating the immune response and protecting against respiratory infections. Vitamin A also has immunomodulatory eff ects, inhibiting viral replication and enhancing immune responses, thereby reducing morbidity and mortality from COVID-19. The aim of research was to study the levels of vitamins A, D, and retinol- binding protein 4 in children with COVID-19, and their associations with the severity of the disease. Material and Methods. 112 children aged 1 month to 18 years with COVID-19 confi rmed by polymerase chain reaction (PCR) in nasal swabs or by a positive serologic test (IgM and IgG or IgM). In all children, vitamin D levels were determined by the colorimetric enzyme- linked immunosorbent assay (ELISA) using the Monobind test system. Vitamin A and retinol binding protein 4 (RBP4) levels were determined by the colorimetric enzyme- linked immunosorbent assay (ELISA) using the Elabscience test system. Statistical analysis was performed using Stat Plus (its 95 % confi dence interval (95 % CI) was calculated for the mean values, and the Kruskal- Wallis test (H-test) was used as the reliability criterion for checking the equality of the medians of several samples). The level of statistical signifi cance was set at P<0.05). The study was conducted in accordance with the rules of patient safety and ethical principles of scientifi c medical research involving human subjects (2000). The permission to conduct this study was granted by the Bioethics Commission (Protocol No. 73, dated April 3, 2023). The parents (legal representatives) of the patients gave their written consent to the conduct of this study. This study is a fragment of research work «Optimizing the diagnosis of clinical and pathogenetic characteristics of the COVID-19 coronavirus infection in children with comorbid pathology and treatment features» (state registration No. 0123U100064, 2023-2025). Results. The mean age of the children was (7.04±5.75) years (95 % CI 5.96-8.12). According to the severity of the disease, 57 children (50.89 %) had a mild course, 43 children (38.39 %) had a moderate course, and 12 children (10.72 %) had a severe course. The concentration of vitamin D in children with mild course of COVID-19 was 30.91 ng/ml, in children with moderate course - 29.10 ng/ml, in children with severe course - 22.42 ng/ml (Р<0.05). The level of vitamin A also varied in children with diff erent severity of the disease: in mild COVID-19 it was 456.10 ng/ml, in moderate - 347.30 ng/ml, and in severe - 242.90 ng/ ml (Р <0.001). At the same time, the level of retinol binding protein 4 was 30.66 ng/ml in mild disease, 33.07 ng/ml in moderate disease and 23.28 ng/ml in severe disease. Conclusions. Children with moderate and severe COVID-19 have signifi cantly lower levels of vitamins A, D, and RBP4 compared to uninfected individuals. Vitamin A and RBP4 levels were age-dependent, and vitamin D levels did not show agerelated patterns. Lower levels of vitamins A and D are associated with higher levels of pro-infl ammatory markers - CRP, leukocytes and ESR.